Effect of Resin Coating and Chlorhexidine on Microleakage of Two Resin Cements after Storage - F. Shafie; M. Doozandeh; A. Alavi (Tehran University of Medical Sciences, 2010)
Objective: Evaluating the effect of resin coating and chlorhexidine on microleakage of two resin cements after water storage. Materials and Methods: Standardized class V cavities were prepared on facial and lingual surfaces of one hundred twenty intact human molars with gingival margins placed 1 mm below the cemento-enamel junction. Indirect composite inlays were fabricated and the specimens were randomly assigned into 6 groups. In Groups 1 to 4, inlays were cemented with Panavia F2.0 cement. G1: according to the manufacturer's instruction. G2: with light cured resin on the ED primer. G3: chlorhexidine application before priming. G4: with chlorhexidine application before priming and light cured resin on primer. G5: inlays were cemented with Nexus 2 resin cement. G6: chlorhexidine application after etching. Each group was divided into two subgroups based on the 24-hour and 6-month water storage time. After preparation for microleakage test, the teeth were sectioned and evaluated at both margins under a 20× stereomicroscope. Dye penetration was scored using 0-3 criteria. The data was analyzed using Kruskal-Wallis and complementary Dunn tests. Results: There was significantly less leakage in G2 and G4 than the Panavia F2.0 control group at gingival margins after 6 months (P<0.05). There was no significant differences in leakage between G1 and G3 at both margins after 24 hours and 6 months storage. After 6 months, G6 revealed significantly less leakage than G5 at gingival margins (P=0.033). In general, gingival margins showed more leakage than occlusal margins. Conclusion: Additionally, resin coating in self-etch (Panavia F2.0) and chlorhexidine application in etch-rinse (Nexus) resin cement reduced microleakage at gingival margins after storage.